If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2n + -1)(2n + -1) + 4(2n + -1) + -12 = 0 Reorder the terms: (-1 + 2n)(2n + -1) + 4(2n + -1) + -12 = 0 Reorder the terms: (-1 + 2n)(-1 + 2n) + 4(2n + -1) + -12 = 0 Multiply (-1 + 2n) * (-1 + 2n) (-1(-1 + 2n) + 2n * (-1 + 2n)) + 4(2n + -1) + -12 = 0 ((-1 * -1 + 2n * -1) + 2n * (-1 + 2n)) + 4(2n + -1) + -12 = 0 ((1 + -2n) + 2n * (-1 + 2n)) + 4(2n + -1) + -12 = 0 (1 + -2n + (-1 * 2n + 2n * 2n)) + 4(2n + -1) + -12 = 0 (1 + -2n + (-2n + 4n2)) + 4(2n + -1) + -12 = 0 Combine like terms: -2n + -2n = -4n (1 + -4n + 4n2) + 4(2n + -1) + -12 = 0 Reorder the terms: 1 + -4n + 4n2 + 4(-1 + 2n) + -12 = 0 1 + -4n + 4n2 + (-1 * 4 + 2n * 4) + -12 = 0 1 + -4n + 4n2 + (-4 + 8n) + -12 = 0 Reorder the terms: 1 + -4 + -12 + -4n + 8n + 4n2 = 0 Combine like terms: 1 + -4 = -3 -3 + -12 + -4n + 8n + 4n2 = 0 Combine like terms: -3 + -12 = -15 -15 + -4n + 8n + 4n2 = 0 Combine like terms: -4n + 8n = 4n -15 + 4n + 4n2 = 0 Solving -15 + 4n + 4n2 = 0 Solving for variable 'n'. Factor a trinomial. (-5 + -2n)(3 + -2n) = 0Subproblem 1
Set the factor '(-5 + -2n)' equal to zero and attempt to solve: Simplifying -5 + -2n = 0 Solving -5 + -2n = 0 Move all terms containing n to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + -2n = 0 + 5 Combine like terms: -5 + 5 = 0 0 + -2n = 0 + 5 -2n = 0 + 5 Combine like terms: 0 + 5 = 5 -2n = 5 Divide each side by '-2'. n = -2.5 Simplifying n = -2.5Subproblem 2
Set the factor '(3 + -2n)' equal to zero and attempt to solve: Simplifying 3 + -2n = 0 Solving 3 + -2n = 0 Move all terms containing n to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -2n = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -2n = 0 + -3 -2n = 0 + -3 Combine like terms: 0 + -3 = -3 -2n = -3 Divide each side by '-2'. n = 1.5 Simplifying n = 1.5Solution
n = {-2.5, 1.5}
| 34=5a+3(2a+7) | | 2*x+5=10 | | 3-log(2x)=1 | | 3-ln(2x)=1 | | y^2+30y+216=0 | | 8x-7w+5x+7y+3y+3w= | | 3*4g=12g | | 3y^2+2xy-x^2=7 | | 4w+2x-y+3w-15x-8y= | | 6x-3y+10w-6y-3w+7x= | | 6(c-1)whenc=6 | | 3w+2y+7x+6x-11y+4w= | | 3w+7x-11y+4w+6x+2y= | | 16(1/2(8)-1) | | 4.9t^2-10.5t-27.3=0 | | 15a+13b+2c+2c-4b-2a= | | x^2-18+48=0 | | 20p+18q+p-4q-7p= | | 3x+5=-7x+12 | | 14m+3n-6m+7n= | | 1/216^2-16 | | 16a+12b+6c+2c-2b-5a= | | 17p+20q+p-4q-7p= | | 15m+5n-5m+11n= | | Log(5x-2)+3=6 | | 12a+11b+5c+6c-4b-2a= | | 17p+20q+p-4q-4p= | | tan(a)=1.04 | | 11m+4m-3m+10n= | | 8x-3y+10x-2y-3y+7x= | | 4w+6y+6x+9x-11y+4w= | | 2x+7=25x |